Complete Poems, by J. G. Ladrón de Guevara (XXI Century. Spanish Literature and Culture, 2025)
Critical commentary on the complete poetry of the Granada poet José G. Ladrón de Guevara (1953-1956), edited by Professor Antonio Chicharro, and published in 2025.